2023
DOI: 10.1021/acs.inorgchem.3c01112
|View full text |Cite
|
Sign up to set email alerts
|

Target-Oriented Synthesis of Borate Derivatives Featuring Isolated [B3O3] Six-Membered Rings as Structural Features

Abstract: Borates provide an excellent platform for investigating the optical nonlinearity and linearity of crystals as photoelectric functional materials. In our work, borate derivatives with isolated [B3O3] six-membered rings as structural features are the preferred system due to their simple functional units and excellent properties. Herein, by utilizing the target-oriented synthesis, a series of borate derivatives, A2[B3O3F4(OH)] (A= NH4, Rb, Cs) (ABOFH), K2.3Cs0.7B3O3F6 (KCsBOF), and Cs3[B3O3(OH)3]Cl3 (CsBOHCl), wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Experimental and theoretical studies have confirmed that B 3 O 3 nanosheets possess a hexagonal planar structure, with strong covalent bonds between the boron atoms. The six-fold symmetry of this structure has been reported in both experimental [33] and theoretical studies [34]. The formation of B 3 O 3 nanosheets occurs through the condensation of three tetrahydroxydiboron molecules [35], which connect six B 3 O 3 hexagons to create a porous structure with a surface area of 2.32 Å.…”
Section: Introductionmentioning
confidence: 72%
“…Experimental and theoretical studies have confirmed that B 3 O 3 nanosheets possess a hexagonal planar structure, with strong covalent bonds between the boron atoms. The six-fold symmetry of this structure has been reported in both experimental [33] and theoretical studies [34]. The formation of B 3 O 3 nanosheets occurs through the condensation of three tetrahydroxydiboron molecules [35], which connect six B 3 O 3 hexagons to create a porous structure with a surface area of 2.32 Å.…”
Section: Introductionmentioning
confidence: 72%
“…Wherein, polymorphism is a very common phenomenon, and Rb 2 [B 3 O 3 F 4 (OH)] was reported to crystallize in centrosymmetric C2/c space group, while RbBOFH in this work crystallizes in noncentrosymmetric Ama2 space group. [13] The split of B( 5) atom causing a mirror in RbBOFH may be the origin of their difference in symmetry.…”
Section: Investigation Of Hydroxyfluorooxoboratesmentioning
confidence: 99%
“…2, 3, 4, 5, 7, 8, 10, 11 8) is situated at the 2 1 helical axis, and the occupancy of H atom is 0.5. Only one unique Cs atom is bonded to one O and eigth F atoms to form the [CsOF 8 ] polyhedron with CsÀ O and CsÀ F bond lengths located at 3.1798 (13) and 3.044(5)-3.368 (4)…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38][39][40][41] Hydroxyfluorooxoborates composed of DUV [B-O-F/OH] units as new potential candidates have been proposed and confirmed. [42][43][44][45][46][47] These new deep UV units in borates provide raw materials for exploring new potential DUV materials. 48 Each addition of a new DUV unit in borates may lead to the discovery of many new materials, and the combination of these old and new moieties greatly enriches the structural chemistry of borates.…”
Section: Introductionmentioning
confidence: 99%
“…31–41 Hydroxyfluorooxoborates composed of DUV [B–O–F/OH] units as new potential candidates have been proposed and confirmed. 42–47 These new deep UV units in borates provide raw materials for exploring new potential DUV materials. 48…”
Section: Introductionmentioning
confidence: 99%